ADOLESCENT KNOWLEDGE AND PERCEPTION OF HIV/ AIDS STIGMATIZATION IN THE INDONESIAN CONTEXT: Hubungan Tingkat Pengetahuan dan Persepsi Remaja Terhadap Stigma Kepada Orang Dengan HIV/AIDS Di Indonesia - Stella Maris Bakara; Elvi Sahara Lubis; Yessy Fitriani (Jurnal Berkala Epidemiologi, 2023)
Background: Stigmatization of People Living with HIV/AIDS (PLWHA) among adolescents today has become a significant barrier to preventing the increase of HIV/AIDS cases, including understanding those at risk and PLWHA themselves. Adolescents' knowledge and perceptions about PLWHA significantly influence HIV/AIDS stigma, given that adolescence signifies a phase of profound biological, psychological, and social transition. Objective: This research aims to determine the correlation between knowledge and perception of the stigma against people living with HIV/AIDS. Methods: This study utilizes secondary data from the Indonesian Demographic and Health Survey (IDHS) 2017, analyzed using a cross-sectional method. The sample consisted of 14,270 adolescents in Indonesia aged 15 to 24 years. The study employed questionnaires on HIV/AIDS knowledge, perception towards PLWHA, and stigma towards PLWHA. Data analysis was conducted using univariate analysis to observe frequency distribution and bivariate analysis with a chi-square test to examine the relationship between two variables. Results: The research results indicate a significant correlation between adolescents' knowledge and stigma towards PLWHA at 0.00 (p<0.05), as well as a significant correlation between adolescents' perception and stigma towards people with HIV/AIDS at 0.00 (p<0.05). Conclusion: Prevention efforts through education and comprehensive approaches in delivering health information in a way that is well-received by adolescents can be presented innovatively.